A simplified formula for the determination of the fundamental period of mixed structures with vertical combination of different seismic resisting systems. (January 2023) - Saadatkhah, Amir; Reza Chenaghlou, Mohammad; Poursha, Mehdi
Abstract: Vertical combination of different seismic resisting systems, permitted in the seismic design codes such as ASCE/SEI7-16, is an effective choice for the structural design of mid- and high-rise buildings. In the seismic analysis of structures, according to the seismic codes, an estimate of the fundamental period of vibration is needed. On other hand, there is no simplified equation to compute the fundamental period of vibration of mixed buildings with vertical combination of different seismic resisting systems. In this study, by using the Rayleigh's method, a simplified formula is proposed for determining the fundamental period of this type of structures. The proposed formula is verified by using the eigenvalue analysis of the mathematical model of the 11 building frames with different structural characteristics along their height. Also, two different mixed structures composed of steel and reinforced concrete moment-resisting frame (MRF) structures as well as of steel concentrically braced frame (CBF) and reinforced concrete MRF structures are examined. The fundamental period of a 3-dimensional (3D) vertically irregular 6-story building with setbacks is also determined to show the efficiency of the proposed method for vertically irregular structures. Furthermore, the proposed formula is verified by the period obtained from an experimental full-scale test of a structure. The results indicate that the proposed formula results in the fundamental period of the mixed structures with satisfactory accuracy. The largest and average errors in the fundamental period of the buildings under consideration, obtained by the proposed formula, are less than 10% and 6%, respectively, compared to the eigenvalue analysis. Therefore, the proposed formula can be used in the seismic evaluation process of existing buildings as well as in the design process of new ones.